Predicción de métricas de red celular basada en información social - Villegas, Javier; Fortes-Rodríguez, Sergio; Baena-Martínez, Eduardo; Barco-Moreno, Raquel (My University, 2020)
Recent years have seen a massive increase of mobile network users, which can overwhelm the network capacities if an unexpectedly large amount of devices connect to it at the same time, resulting in lower quality of service. Thus, this makes useful the application of forecasting mechanisms for cellular network management activities. Vast cellular demands and social events are strongly correlated, and these events can be rapidly gathered from Internet sources. Therefore, this paper proposes a model to exploit these resources to make long-term cellular demand prediction.
Keywords: Sistemas de comunicaciones móviles; Previsión tecnológica; 5G; Social events; Forecasting; Machine Learning; Cellular networks